Ukraine – Ukrzaliznytsia Modernization Strategy : Policy Note 4 – Debt Management - World Bank Group (World Bank, Washington, DC, 2019)
This note focuses on the current debt situation of UZ, the associated risks and ways to manage them. It does not address broader financial sustainability issues and how to finance the investment backlog. This is of paramount importance and should be a priority for future work. This note uses an analysis of the available audited financial statements in the January 1, 2014 -June 30, 2018 period to discuss risks and concerns regarding the financial viability of the UZ going forward given the near-critical liquidity situation and widespread solvency concerns in the financial markets. This note suggests some steps for ameliorating the present dire liquidity situation: (i) A clear market opening and corporate restructuring strategy; (ii) detailed review of the asset valuation exercise carried out by reputable asset evaluators; (iii) based on the results of asset revaluation, seek Government consent to sell non-core assets and (iv) seek support in raising substantial investment resources at reasonable cost necessary to carry out the adopted modernization strategy and reach sustainable levels of business operation in the medium-to-longer run (such as increasing the share of current assets by selling non-core fixed assets such as land and buildings). Any sustainable solution going forward, hinges on an open commitment to market opening and deep organizational and management restructuring programs discussed in other policy notes. Given the ownership structure, political and social importance of UZ, and the legal status of the company, this cannot be done without full ownership and support of the government (including the Ministry of Finance). Additionally, given the size of the company and present institutional and governance risks, successful restructuring and changed perception of domestic and international financial markets will critically depend on the credibility of the program.